Dysregulated autophagic activity induced in response to chronic intermittent hypoxia contributes to the pathogenesis of NAFLD - Wang, Dong; Si, Dongyu; Li, Gang; Ding, Zhimin; Yang, Xiaonan; Gao, Chaobing (Frontiers in Physiology, 2022)
Chronic intermittent hypoxia (CIH) is a pathological characteristic of obstructive sleep apnea (OSA) that has been linked to the pathogenesis of nonalcoholic fatty liver disease (NAFLD). The specific link between CIH, autophagic activity, and NAFLD, however, has not previously been characterized. The goal of this study was to assess the relationship between CIH-induced autophagy and the pathogenesis of OSA-associated NAFLD. Western blotting was used to assess the expression of proteins associated with lipid synthesis, endoplasmic reticulum (ER) stress, and autophagic activity. To establish an in vivo model system, C57BL/6 mice were subjected to CIH conditions for 8 h per day over a 12-week period, and were administered chloroquine (CQ) for 1 week prior to euthanization. Levels of serum and liver triglycerides in these animals were assessed, as were proteins related to hepatic autophagy, ER stress, and lipogenesis. qPCR was additionally used to assess hepatic inflammation-related gene expression, while transmission electron microscopy was used to monitor lipid droplet (LD) accumulation and ER morphology. OSA patients and CIH model mice exhibited increases in the expression of proteins associated with hepatic autophagy, ER stress, and lipogenesis. CIH was also associated with more pronounced LD accumulation, hepatic inflammation, and hepatic steatosis in these mice. While serum and hepatic TG and TC levels and serum ALT/AST were increased in response to CIH treatment, the administration of CQ to these mice led to reductions in ER stress-related proteins (XBP1, IRE1α, EIF2α) and lipogenesis-related proteins (ACC, SCD1, FASn), in addition to significantly reducing hepatic inflammation, steatosis, and LD accumulation in these animals. These results suggest that persistent CIH can drive dysregulated hepatic autophagic activity, hepatic steatosis, and ER stress, highlighting potential targets for therapeutic intervention aimed at preventing or treating OSA-associated NAFLD.